1998
DOI: 10.1152/ajpcell.1998.274.4.c1075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proximal tubular fluid absorption by nitric oxide and atrial natriuretic peptide in rat kidney

Abstract: Atrial natriuretic factor (ANF) and nitric oxide (NO) stimulate production of guanosine 3′,5′-cyclic monophosphate (cGMP) and are natriuretic. Split-drop micropuncture was performed on anesthetized rats to determine the effects of ANF and the NO donor sodium nitroprusside (SNP) on proximal tubular fluid absorption rate ( J va). Compared with control solutions, SNP (10−4 M) decreased J va by 23% when administered luminally and by 35% when added to the peritubular perfusate. Stimulation of fluid uptake by lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 30 publications
3
64
2
Order By: Relevance
“…We now believe the partial to substantial recovery of NO during elevated NaCl concentration at both 400 and 600 mOsm reflected the cells were simply expressing a decreased entry of sodium into the cells as part of feedback suppression of sodium entry into the cells. Studies by Levine et al [12], Ortiz et al [13], Roczniak and Burns [9], and Eitle et al [14] have shown NO suppresses transport of sodium ions in a negative feedback scenario and this area has been reviewed by Liang and Knox in 2000 [15]. From our observations, a similar process occurs in tissue slice specimens and is particularly apparent with low sodium stress conditions, such as 400 mOsm NaCl.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We now believe the partial to substantial recovery of NO during elevated NaCl concentration at both 400 and 600 mOsm reflected the cells were simply expressing a decreased entry of sodium into the cells as part of feedback suppression of sodium entry into the cells. Studies by Levine et al [12], Ortiz et al [13], Roczniak and Burns [9], and Eitle et al [14] have shown NO suppresses transport of sodium ions in a negative feedback scenario and this area has been reviewed by Liang and Knox in 2000 [15]. From our observations, a similar process occurs in tissue slice specimens and is particularly apparent with low sodium stress conditions, such as 400 mOsm NaCl.…”
Section: Discussionsupporting
confidence: 77%
“…Using isolated thick ascending limb tubules of the rat, Ortiz et al [13] have shown NaCl increased NO production that suppressed the Na + /K + /2Cl + cotransport to limit further sodium uptake. In this same context, Eitle et al [14] using in vivo split droplet techniques in rat proximal tubules and Roczniak and Burns [9] using isolated rabbit proximal tubules found exogenous NO decreased NaCl coupled fluid transport and cell uptake of sodium. These various studies support the evolving hypothesis that entry of sodium ions into tubular cells initiated a set of mechanisms that used NO to suppress further sodium absorption.…”
Section: Introductionmentioning
confidence: 95%
“…The rats were adapted to the cages by being restrained for 2 h on 2 consecutive days before the final collection day to obtain unstressed conditions. Briefly, 14 [C]tetraethylammonium bromide clearance was used as a marker for the effective renal plasma flow (ERPF), 3 [H]inulin clearance as a marker for the GFR, and lithium clearance (C Li) as a marker for the outflow of tubular fluid from the proximal tubules. Renal clearances (C) and fractional excretions (FE) were calculated by the standard formulas…”
Section: Seriesmentioning
confidence: 99%
“…However, besides the circulatory effects, NO also exerts direct effects on renal tubular function, including an inhibitory action on proximal tubular sodium handling. Excess NO has been shown to inhibit the Na-K-ATPase and the type 3 sodium/proton exchanger (NHE3) in proximal tubular cell lines (20,33,46), and micropuncture studies in rats have shown that NO significantly decreases proximal tubular fluid reabsorption (14,61). These micropuncture data from rats are supported by studies in humans showing that systemic administration of NOS inhibitors decreases fractional excretion of sodium (FE Na ) and fractional excretion of lithium (FE Li ; an index for the delivery of tubular fluid out of the proximal tubules) (4,6,36).…”
mentioning
confidence: 99%
“…NO-induced natriuresis and diuresis can occur in the absence of hemodynamic changes, indicating that NO directly inhibits Na and water absorption along the nephron. In vitro studies have shown that NO blunts transport in isolated proximal tubules (1), cortical collecting ducts (3,39,40), inner medullary collecting ducts (2), and thick ascending limbs (2,34,35). Additionally, NO has been reported to inhibit Na transport in several cultured renal cells (5,15,16).…”
mentioning
confidence: 99%